GoHoliday: Development of An Improvised Mobile Application for Boutique Hotels and Resorts - Iftiaj Alom; Ismail Ahmed Al-Qasem Al-Hadi; Neesha Jothi; Sook Fern Yeo (Journal of Informatics and Web Engineering)
One of the main challenges boutique hotels and resorts face is the direct outreach to tourists and customers. As a result, these independent hotels often resort to online platforms such as Agoda and Airbnb to expand their customer base. However, this approach comes at the cost of losing revenue to Online Travel Agencies (OTAs) that solely focus on room sales, hindering the establishment of a strong brand image for boutique hotels and resorts. Considering the heavy reliance on OTAs, this paper focuses on the development of GoHoliday, a cross-platform mobile app prototype that aims to bridge the gap between boutique hotels and users. This mobile application seamlessly integrates a booking engine, an AI assistant for trip planning, and an experience-sharing platform, enhancing the app's capabilities alongside other features. By implementing the GoHoliday mobile application, boutique hotels can maximize their reach and establish a distinct brand identity by directly serving their valuable guests with more personalized arrangements.